Association of Serum Creatinine and Cortical Thickness with Renal Echogenicity on Ultrasound in Chronic Kidney Disease: Association of Serum Creatinine and Cortical Thickness with Renal Echogenicity on Ultrasound - Iram, Maria; Atta, Muhammad Fahad; Mujahid, Naima; Aslam, Sumaira; Safdar, Saba Saleem; Anwar, Khawar (Pakistan Journal of Health Sciences, 2025)
The Incidence of chronic kidney disease (CKD) is increasing day by day all over the globe. In assessing the progression of CKD, both the function and structure of the kidney need to be evaluated. Objectives: To determine the association between serum creatinine and cortical thickness with renal echogenicity on ultrasound in patients with CKD. Methods: This cross-sectional analytical research was carried out at the Department of Radiology and Biochemistry, Shahida Islam Medical and Dental College, Lodhran, for six months (June 2024 to November 2024). All patients who were referred for ultrasonography of the kidneys, with serum creatinine and serum urea checked on the same day on which U/S was carried out, were included. Patients who were k/c of acute renal injury, on hemodialysis, peritoneal dialysis, renal transplant, chronic liver disease, fatty liver, or those having a solitary kidney were all excluded. SPSS version 23.0 was used for data analysis. A one-way ANOVA test was applied to test for association, keeping p<0.05 statistically significant. Results: Mean age of participants was 52.26 ± 12.50 years (95% CI: 39.76–64.76). The study found that higher serum creatinine and urea levels were significantly associated with increased cortical echogenicity and reduced cortical thickness on ultrasound. The mean serum creatinine was 2.11 ± 1.2 mg/dL, and cortical thickness progressively declined from 1.11 cm to 0.71 ± 0.10 cm across echogenicity grades. Conclusions: The study found a significant association between elevated serum creatinine and cortical thickness levels with renal echogenicity on ultrasound in CKD patients.